The Influence of Transformational Leadership on the Performance of Lecturers and Educators with Learning Organization as an Intervening Variable Midwifery Academy Kharisma Husada Binjai - Handayani, Rika; Isa Indrawan, Muhammad (CV. Lafadz Jaya, 2023)
The purpose of this study was to determine and analyze the effect of Transformational Leadership on Lecturer Performance through Learning Organizations. The location of this research was conducted at the Kharisma Husada Binjai Midwifery Academy. The population is 70 employees, and the sampling technique is a saturated sample. The research model used is path analysis and measuring tools using Smart PLS version 3.3.3. The results of this study are that Transformational Leadership has a positive and significant effect on Lecturer Performance. Transformational leadership has a positive and significant effect on organizational learning. Organizational learning has a positive and significant effect on lecturer performance. Transformational leadership has a positive and significant effect on lecturer performance through organizational learning.